2015 International Conference on Developments of E-Systems Engineering (DeSE) 2015
DOI: 10.1109/dese.2015.58
|View full text |Cite
|
Sign up to set email alerts
|

Technology Acceptance Model for the Use of M-Health Services among Health Related Users in UAE

Abstract: Abstract-This paper aims to identify the main factors that influence health related users' acceptance to mobile health services technology as a mean for receiving general health services. This study proposes Technology Acceptance Model (TAM) modified by incorporating external variables including perceived security and perceived trust in order to determine the factors that mostly influence the intention to use M-Health services. In this study, the proposed research model and hypotheses tested and validated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 11 publications
5
23
1
3
Order By: Relevance
“…Therefore, H2 is supported. This finding is in line with the findings of (Alloghani et al, 2015) and (Sun et al, 2013) who believe that the perceived ease of use is an important indicator that influences the intention to use the mobile health services. The interface design and features of the app are therefore important because the likelihood of app adoption for the patient increases when less effort is required, the operation is easy to learn, and satisfying user experience is possible.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, H2 is supported. This finding is in line with the findings of (Alloghani et al, 2015) and (Sun et al, 2013) who believe that the perceived ease of use is an important indicator that influences the intention to use the mobile health services. The interface design and features of the app are therefore important because the likelihood of app adoption for the patient increases when less effort is required, the operation is easy to learn, and satisfying user experience is possible.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the findings of SmartPLS, the result showed that the perceived usefulness actually has a significant positive relationship (t-value = 4,399, α = 0.05, one-tailed test) with the patient's behavioral intention to use the mobile health app, H1 is therefore supported. This finding is in line with the findings of (Nasir and Yurder, 2015), (Deng et al, 2012) and (Alloghani et al, 2015) where the perceived usefulness has a positive effect on the patient's behavioral intention to use the mobile health apps. Patients will have a more positive attitude towards the mobile health app if the app is so useful that the user can effectively control their health care (Nasir and Yurder, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is important to note that applications do not replace consultation and guidance from a professional, such as a doctor or nutritionist. Also, it is necessary to check with caution the source and reliability of the information offered by this app, guides Fortes (Alloghani, et al, 2015).…”
Section: Parallel Use To Health Professionalmentioning
confidence: 99%